The Effect of Monetary Policies on Unemployment under Inflation Uncertainty: Case Study of IRAN - Sohrab Delangizan; MOHAMMAD KARIMI; Parastoo Amiriani (پژوهشهای اقتصادی, 2017)
This research examines the effect of monetary policies on unemployment under inflation uncertainty in Iran using the annual data during 1974-2011. The basic model is selected according to the simultaneous equilibrium of dynamic aggregate demand and supply. In addition, inflation uncertainty is calculated using the GARCH family models including ARCH, GARCH and EGARCH. The generated data from a novel model is considered as a proxy for inflation uncertainty, and Generalized Method of Moments (GMM) is used to estimate this model. The estimation results show that inflation uncertainty reduces the unemployment rate, i.e. the effect of monetary policies on unemployment is decreased under inflation uncertainty, and there is a significant and positive relationship between unemployment and inflation rates. Henceforth, an increase in inflation uncertainty leads to an increase in unemployment rate, which is in line with Friedman's theory in this field